O consumo serve para pensar : revista Recreio, crianças e alternativas para a formação de cidadãos - Correia, Ligia Stella Baptista (2010)
This dissertation seeks to relate consumption and childhood to a cultural industry in particular - Editora Abril - from the perspective of children's magazines and investigates if its core product, Recreio magazine, has a proposal to encourage citizenship by opening spaces for children's participation in the magazine. The public spaces for citizens‟ participation are not always open and accessible; on market environment as consumer market‟s. On this field some industries have been trying to answer the consumers demand therefore, keeping some contact channels.. Relating to media, have been gaining space, those which use digital technologies to enable larger access to users, allowing them to express their opinions, and through it, fans and consumer communities tend to unite, becoming stronger, producing new content and influencing producers. The hypothesis discussed here is that, during convergence culture times, users would not be audience only anymore and will also become producers. The access to those technologies and the initiative to participate takes a while to reach a large number of people. Never then less , if this participation becomes stimulated by the media and also by the government policies directed to childhood, the number of active children might increase significantly. This research has the objective to map existing opportunities on child magazines, and specifically on Recreio magazine, to stimulate the reader to assume its possible condition to produce content. In order to achieve that, a brief background of Brazilian child magazines was built, starting with an analysis of the first version of Recreio magazine: The toy magazine, which was in the market from 1969 to 1982 and is used as a comparative basis to the actual version of the same magazine, published by Editora Abril and released on March 2000. The field research is focused initially in the reading of 985 magazine sold copies; the construction of the background report and the selection of 10 magazine numbers which were sold from March and May of 2010,to deeper analysis, was the result of this process. Among the authors who guide theory and concepts highlight: from the consumption point of view, Canclini (2006;2008), for childhood, Buckingham (2007), and digital medias, Jenkins (2009)